Exosomes Secreted From Bone Marrow Mesenchymal Stem Cells Attenuate Oxygen-Glucose Deprivation/Reoxygenation-Induced Pyroptosis in PC12 Cells by Promoting AMPK-Dependent Autophagic Flux - Zeng, Qing; Zhou, Yuqing; Liang, Donghui; He, He; Liu, Xiaoli; Zhu, Rui; Zhang, Meimei; Luo, Xun; Wang, Yao; Huang, Guozhi (Frontiers in Cellular Neuroscience, 2020)
Background: Cerebral ischemia reperfusion (I/R) injury can lead to severe dysfunction, and its treatment is difficult. It is reported that nucleotide-binding domain leucine-rich repeats family protein 3 (NLRP3) inflammasome-mediated cell pyroptosis is an important part of cerebral I/R injury and the activation of autophagy can inhibit pyroptosis in some tissue injury. Our previous study found that the protective effects of bone marrow mesenchymal stem cells (BMSCs) in cerebral I/R injury may be associated with the regulation of autophagy. Recent studies have demonstrated that exosomes secreted from BMSCs (BMSC-Exos) may play an essential role in the effective biological performance of BMSCs and the protective mechanism of BMSC-Exos is associated with the activation of autophagy and the remission of inflammation, but it has not been reported in studies of cerebral I/R injury. We aimed to investigate the effects of BMSC-Exos on cerebral I/R injury and determine if the mechanism is associated with the regulation of pyroptosis and autophagic flux. Method: PC12 cells were subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) to induce cerebral I/R in vitro and were co-cultured with BMSC-Exos. Cell viability was determined with CCK-8 and lactate dehydrogenase detection kits. Scanning electron microscopy, Hoechst 33342/propidium iodide double staining, 2’, 7’-dichlorodihydrofluorescein diacetate assay, immunofluorescence, Western blot and enzyme-linked immunosorbent assay were used to detect cell pyroptosis. Furthermore, transmission electron microscopy, GFP-RFP-LC3 adenovirus transfection and Western blot were used to detect autophagic flux and its influence on pyroptosis. Finally, coimmunoprecipitation was used to detect the binding interaction between NLRP3 and LC3. Results: BMSC-Exos increased cell viability in OGD/R. The inhibitory effect of BMSC-Exos on pyroptosis was comparable to the NLRP3 inhibitor MCC950 and was reversed by NLRP3 overexpression. Furthermore, BMSC-Exos promoted autophagic flux through the AMP-activated kinase (AMPK)/mammalian target of rapamycin pathway, whereas chloroquine, AMPK silencing and compound C blocked the inhibitory effect on pyroptosis. Conclusions: BMSC-Exos can protect PC12 cells against OGD/R injury via attenuation of NLRP3 inflammasome-mediated pyroptosis by promoting AMPK-dependent autophagic flux.